2017
DOI: 10.5324/njsts.v5i2.2314
|View full text |Cite
|
Sign up to set email alerts
|

Crafting sustainability? An explorative study of craft in three countercultures as a learning path for the future

Abstract: This article explores and seeks to identify what 'crafting sustainability' could mean in relation to education for sustainable development (ESD). Certain ESD craft pedagogies are explored in three countercultures (from 1900, 1968 and 2017 Licensing:All content in NJSTS is published under a Creative Commons Attribution-ShareAlike 4.0 license. This means that anyone is free to share (copy and redistribute the material in any medium or format) or adapt (remix, transform, and build upon the material) the material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 2 publications
0
10
0
2
Order By: Relevance
“…As Van Poeck and Lysgaard (2016, p. 305) correctly point out, sustainable development involves different solutions to societal and controversial issues, so it is not entirely clear how this should be reflected in the training system. Hofverberg et al (2017) substantiated the claim that improved arts education can solve certain problems on the path to sustainable development of society. For example, prospective designers may be involved in the production of functional or ecological products.…”
Section: Interdependence Of Arts Education and Sustainable Developmentmentioning
confidence: 81%
“…As Van Poeck and Lysgaard (2016, p. 305) correctly point out, sustainable development involves different solutions to societal and controversial issues, so it is not entirely clear how this should be reflected in the training system. Hofverberg et al (2017) substantiated the claim that improved arts education can solve certain problems on the path to sustainable development of society. For example, prospective designers may be involved in the production of functional or ecological products.…”
Section: Interdependence Of Arts Education and Sustainable Developmentmentioning
confidence: 81%
“…While arguing there are no objective criteria for creativity assessment, one should point to the important function of cultural development strategies as the key factor of a sustainable city transition. The social consensus concerning the estimation of the potential of the creative urban spaces has provided a platform not only for meetings of countercultures, but also for developing a sustainable city [26].…”
Section: Creative Urban Sustainability Transitionmentioning
confidence: 99%
“…Research (Boehnert 2015; Hofverberg et al. 2017) shows that when design and crafting is made as an activity for sustainability, there are many possible contents that point to different, and sometimes conflicting, sustainability goals. This is also confirmed in our findings; for example, ‘sustainable’ materials can mean many different things as well as what it means to become a ‘sustainable’ maker.…”
Section: Consequences and Further Research For Teaching Esd In Design And Craftmentioning
confidence: 99%
“…When arts education, specifically design and craft, is considered as ESD, Hofverberg et al. (2017) has shown that the educational activity can point to different sustainability goals. For example, a possible ESD content of teaching and learning design and crafting may involve making long‐lasting or functional products, but an ESD content can also point to what one should learn in the making activity, such as the capability to be creative or knowledge of the whole crafting process.…”
Section: Introductionmentioning
confidence: 99%